Concerns, perceived need and competing priorities: a qualitative exploration of decision-making and non-participation in a population-based flexible sigmoidoscopy screening programme to prevent colorectal cancer. Issue 11 (11th November 2016) - Hall, N; Birt, L; Rees, C J; Walter, F M; Elliot, S; Ritchie, M; Weller, D; Rubin, G
Abstract : Objective: Optimising uptake of colorectal cancer (CRC) screening is important to achieve projected health outcomes. Population-based screening by flexible sigmoidoscopy (FS) was introduced in England in 2013 (NHS Bowel scope screening). Little is known about reactions to the invitation to participate in FS screening, as offered within the context of the Bowel scope programme. We aimed to investigate responses to the screening invitation to inform understanding of decision-making, particularly in relation to non-participation in screening. Design: Qualitative analysis of semistructured in-depth interviews and written accounts. Participants and setting: People from 31 general practices in the North East and East of England invited to attend FS screening as part of NHS Bowel scope screening programme were sent invitations to take part in the study. We purposively sampled interviewees to ensure a range of accounts in terms of beliefs, screening attendance, sex and geographical location. Results: 20 screeners and 25 non-screeners were interviewed. Written responses describing reasons for, and circumstances surrounding, non-participation from a further 28 non-screeners were included in the analysis. Thematic analysis identified a range of reactions to the screening invitation, decision-making processes and barriers to participation. These include a perceived or actual lack of need; inability to attend; anxiety and fear about bowel preparation, procedures or hospital; inability or reluctance to self-administer an enema; beliefs about low susceptibility to bowel cancer or treatment and understanding of harm and benefits. The strength, rather than presence, of concerns about the test and perceived need for reassurance were important in the decision to participate for screeners and non-screeners. Decision-making occurs within the context of previous experiences and day-to-day life. Conclusions: Understanding the reasons for non-participation in FS screening can help inform strategies to improve uptake and may be transferable to other screening programmes.